RESILIENCE SYSTEM OF COMPLEX AGROFORESTRY WITH ALBIZIA AS THE MAIN STAND IN WEST JAVA - Marcellinus M.B Utomo (Balai Litbang Teknologi Agroforestry, Ciamis, 2020)
The dynamics in forest management in general as well as in agroforestry are always associated with ecological and social changes. For more than 30 years, the common pattern of community forests especially in West Java applies a complex agroforestry pattern. Currently, one of the most popular trees is albizia (Falcataria moluccana). However, in the past years, gall rust attack becomes a serious problem for the farmers. By borrowing a resilience system approach, this paper describes how a complex agroforestry resilience system with albizia as the primary stand is working in relation to providing sustainable livelihoods so far for the complex agroforestry farmers with all the dynamics especially in the last 10-20 years particularly related to gall rust attack. By selecting a research site in the village of Kalijaya, Ciamis District, West Java Province, this paper aims to understand how the resilience system works in this landscape. The understanding will be a baseline propose some recommendations for the landscape of the villages of Kalijaya specifically and the same type community forests in West Java in general in order to make agroforestry landscapes remain capable or even improving the farmer livelihood by anticipating various threats that may occur in the future by taking into consideration the role that can be undertaken by agroforestry-related parties.